2010
DOI: 10.1177/147470491000800213
|View full text |Cite
|
Sign up to set email alerts
|

Remembering Helpers and Hinderers Depends on Behavioral Intentions of the Agent and Psychopathic Characteristics of the Observer

Abstract: Individual differences in proneness towards granting benefits (i.e., helping) or imposing costs (i.e., hindering) may have led to processes that detect and remember people who are prone to help or hinder. We examined two factors that might influence such memory: the intentionality of the acts and individual differences in psychopathy characteristics. Participants viewed several videos of computer-animated agents that helped or hindered another agent, either intentionally or unintentionally. Afterward, particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Attention to body language, which is indicative of vulnerability, would give psychopathic perpetrators a definite advantage in selecting “easy” victims. In support, previous research indicates that psychopathic traits are associated with better memory for exploitable behavior (Camilleri, Kuhlmeier, & Chu, 2010) and greater accuracy in judging others’ assertiveness (Book, Quinsey, & Langford, 2007) and vulnerability to victimization (Wheeler et al, 2009). While the first study (Wheeler et al, 2009) employed an undergraduate sample to test whether psychopathic traits are associated with increased accuracy in victim selection, we extend the scope by utilizing a sample of violent inmates.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Attention to body language, which is indicative of vulnerability, would give psychopathic perpetrators a definite advantage in selecting “easy” victims. In support, previous research indicates that psychopathic traits are associated with better memory for exploitable behavior (Camilleri, Kuhlmeier, & Chu, 2010) and greater accuracy in judging others’ assertiveness (Book, Quinsey, & Langford, 2007) and vulnerability to victimization (Wheeler et al, 2009). While the first study (Wheeler et al, 2009) employed an undergraduate sample to test whether psychopathic traits are associated with increased accuracy in victim selection, we extend the scope by utilizing a sample of violent inmates.…”
supporting
confidence: 71%
“…Some researchers have examined whether psychopathic traits are correlated with the ability to remember targets that may be more or less exploitable. For example, Camilleri et al (2010) found that psychopathic traits were associated with better memory for “helpers” (i.e., objects that assisted another object in attaining a goal), versus “hinderers” (i.e., objects that prevented another object from attaining a goal). This study offers initial support for earlier descriptions of psychopaths as effective social predators (Hare, 1991; Mealey, 1995), suggesting that psychopaths may be more likely to target “altruistic” people given their increased exploitability.…”
Section: Psychopathy and Victim Selectionmentioning
confidence: 99%
“…They theorized this attentional shift may be the result of deficits in empathy that cause them to experience reduced aversive response, and even potential enjoyment, of others’ distress. The tendency for psychopaths to remember “helpers” more often than “nonhelpers,” may be because they assume altruistic actors are easier to victimize and are, therefore, worth remembering (Camilleri, Kuhlmeier, & Chu, 2010). In fact, individuals who engage in “risky” altruistic behavior are more likely to be victimized than those who do not (Homant, 2010).…”
Section: Psychopathy and Victimizationmentioning
confidence: 99%
“…Psychopathic individuals who are proficient in nonverbal decoding of facial affect may be better able to decode nonverbal information in gait cues. They may also pay greater attention to victims or individuals they believe are vulnerable to victimization (Camilleri et al, 2010) due to empathy deficits (Levenston et al, 2000). Therefore, psychopathic individuals who are lower in empathy may pay particular attention to individuals they perceive as vulnerable and consequently be better at identifying said individuals.…”
Section: The Current Studymentioning
confidence: 99%
“…For instance, whereas mistaking one's hose for a snake could lead to the death of one's lawn, mistaking a snake for one's hose could lead to the death of one's self: arguably a far more negative outcome. Perhaps due to this cost differential, typically-developing adults tend to over-attribute agency to entities in the world, regularly ascribing perceptions, intentions, and beliefs to mechanistic objects like computers, to meteorological events like tornadoes, and to random acts of chance like winning the lottery [6] [13] . This global tendency to attribute agency to non-agents appears to have a parallel in how actual agentive actions are processed: adults display enhanced memory for individuals who helped or hindered a third party intentionally versus accidentally [14] .…”
Section: Introductionmentioning
confidence: 99%